2015
DOI: 10.24966/orp-2052/10004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experiences and Midterm Results of the Treatment of Clubfoot with the Ponseti Method

Abstract: IntroductionTalipes Equinovarus (TEV) is a fairly common birth defect in which males are affected twice as often as females and 50% of the cases show bilateral defects [1]. In the United States, the overall prevalence of clubfoot is 1.29 per 1000 live births [2].Although the Ponseti method of treatment was first described many years ago, it recently became the standard method of treating TEV due to its successful long-term results.Several scoring methods have been developed to assess the foot before, during, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…The findings regarding laterality in our study was not different from other epidemiologic studies but a study by Sayit and Sayit (2015) reported the incidence of foot affected amongst and within the gender, their findings was similar to our study. The tendency that the foot affected would be right or left was not statistically significant.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The findings regarding laterality in our study was not different from other epidemiologic studies but a study by Sayit and Sayit (2015) reported the incidence of foot affected amongst and within the gender, their findings was similar to our study. The tendency that the foot affected would be right or left was not statistically significant.…”
Section: Discussionsupporting
confidence: 78%
“…The Atypical variety is syndromic and is associated with other congenital malformations. There are various scoring systems but the most commonly used is the Pirani scoring and its modifications, also the Dimeglio scoring system (Werler et al, 2013;Sayit and Sayit, 2015;Adegbehingbe et al, 2015;Lynn,2009;www.global-help.org).…”
Section: Introductionmentioning
confidence: 99%